2012
DOI: 10.4081/mi.2012.e21
|View full text |Cite
|
Sign up to set email alerts
|

Stress-sensitive neurosignalling in depression: an integrated network biology approach to candidate gene selection for genetic association analysis

Abstract: Genetic risk for depressive disorders is poorly understood despite consistent suggestions of a high heritable component. Most genetic studies have focused on risk associated with single variants, a strategy which has so far only yielded small (often non-replicable) risks for depressive disorders. In this paper we argue that more substantial risks are likely to emerge from genetic variants acting in synergy within and across larger neurobiological systems (polygenic risk factors). We show how knowledge of major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…From a biological perspective, it is plausible that this may function via the lowered serotonin transcription associated with the s-allele of 5-HTTLPR, leading to reduced availability of a key neurotransmitter in the stress response system (van Eekelen et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…From a biological perspective, it is plausible that this may function via the lowered serotonin transcription associated with the s-allele of 5-HTTLPR, leading to reduced availability of a key neurotransmitter in the stress response system (van Eekelen et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Another factor to be considered is that one of the main risk factors for depression is chronic stress [178]. In this respect, it has been suggested that chronic stress, by increasing nervous system susceptibility, could be a causal factor for neurodegeneration in PD [179,180].…”
Section: Depressionmentioning
confidence: 99%
“…Serotonin plays a role in mood regulation, appetite, and weight ( Blundell, 1984 ; Leibowitz and Alexander, 1998 ; Kalra et al, 1999 ; Ruhé et al, 2007 ), all known to be involved in eating pathology. Serotonin is also involved in the stress-response system ( Gotlib et al, 2008 ; van Eekelen et al, 2012 ), and as 5-HTTLPR is a functional polymorphism it may conceivably play a role in EDs, directly or indirectly through interaction with other environmental stressors. However, in other fields of psychiatry, the role of 5-HTTLPR in moderating the effects of environmental stressors remains controversial; for example, in depression, where independently conducted meta-analysis continue to contradict one another (cf.…”
Section: Introductionmentioning
confidence: 99%